Spatiotemporal evolution of ecosystem service values in an area dominated by vegetation restoration: Quantification and mechanisms - Han, Xiaojia; Yu, Jialuo; Shi, Lin'na; Zhao, Xiaocui; Wang, Jijun (Ecological indicators, 2021)
•The long term spatiotemporal characteristics of ecosystem service value are revealed.•Socio economic factors in ecological restoration are considered in evaluation model.•The spatial differentiation mechanisms of ecosystem service value are identified. The Grain to Green Program (GTGP) has directly led to large-scale transformational land use/cover changes and has impacted ecosystem services. Therefore, it is of great importance to determine the relationship between the land use change and ecosystem services in retired farmland areas. Based on multi-temporal land use data (1980, 1990, 1995, 2000, 2005, 2010, 2015, and 2018), the benefit transfer method was used to calculate the ecosystem service value (ESV), and the willingness to pay and ability to pay were then integrated into the evaluation model. In addition, we used the exploratory spatial data analysis method to systematically analyze the change characteristics of the land use and ESV. Finally, the spatial differentiation mechanisms of the ESV were identified using geographical detectors. The results showed that the transformation of the land use mainly occurred in the farmland, forestland, and grassland; the farmland showed a decreasing trend from 1980 to 2018, whereas the areas of the forestland and grassland showed an increasing trend. The ESV demonstrated an increasing trend during 1980–2018 and formed a spatial pattern with the distribution of high and low values. There was a significant positive spatial correlation in the ESV, and this spatial aggregation became increasingly intense with time. The order of different ecosystem services in the study area was as follows: regulating service > supporting service > provisioning service > cultural service, and the ecosystem service values showed an upward trend, except for the provisioning service that showed a downward trend. The spatial differentiation of the ESV is the result of a combined effect of natural factors and socioeconomic factors. With the restoration of vegetation in the retired farmland area, natural factors such as slope and elevation play a crucial role in the differentiation of the ESV.